PERBANDINGAN EFEKTIVITAS EKSTRAK Sea sponge (Aplysina Fistularis) DAN KOMBINASI EKSTRAK Sea sponge (Aplysina Fistularis) DENGAN ANTIBIOTIK KLORAMFENIKOL TERHADAP BAKTERI Salmonella typhi PADA MEDIA AGAR SECARA IN VITRO - Dhea Kharisma Ardelia (Fakultas Kedokteran, Universitas Hang Tuah, 2024)
Background : Typhoid fever is an infectious disease caused by Salmonella typhi bacteria. Multi Drug Resistance causes immunity to several antibiotics in the treatment of typhoid fever. Sea sponge (Aplysina fitularis) is one of the marine biota and contains compounds that function as antibacterials. Purpose : This study aims to determine the comparison of the effectiveness of Sea sponge extract (Aplysina fitularis) and the combination of Sea sponge extract (Aplysina fitularis) with chloramphenicol antibiotics against Salmonella typhi bacteria. Method : This research is a laboratory experimental research with posttest only control group design. There were four groups of extracts with concentrations of 25%, 50%, 75%, 100% and four groups of extract combinations with chloramphenicol with concentrations of 25%, 50%, 75%, 100% and two control groups, negative (DMSO 0.2%) and positive (chloramphenicol). Result : The average diameter of the inhibition zone with a concentration of 25%, 50%, 75%, 100% and negative control was 6.00 mm, the combination of Sea sponge extract (Aplysina fistularis) and chloramphenicol with a concentration of 25% was 25.95 mm, a concentration of 50% was 26.47 mm, a concentration of 75% was 28.74 mm, a concentration of 100% was 35.84 mm and positive control was 33.25 mm. Data analysis used Kruskal-Wallis test with p=0.001. Conclusion : The combination of Sea sponge extract (Aplysina fistularis) with chloramphenicol has greater effectiveness against Salmonella typhi compared with Sea sponge extract (Aplysina fistularis).